The Effects of Education Level, Health, and Minimum Wage on Labor Productivity - Clarissa Adventri; Syafitri, Wildan (Journal of Development Economic and Social Studies, 2025)
Labor productivity is a major factor in measuring economic growth in a country. According to Human Capital theory and Efficiency Wage Theory, one of the factors that affect labor productivity is education, health, and wages. However, this is not in line with the phenomenon that exists in DIY Province, where with a high level of education and health still makes DIY province as the province with the lowest productivity level in Java Island. This study aims to analyze the effect of education, health, and wages on labor productivity of districts/cities in DIY Province. This research uses an associate quantitative approach with secondary data obtained from the Ministry of Manpower of the Republic of Indonesia and the Central Bureau of Statistics of Yogyakarta Special Region, 2013-2023. Data analysis used multiple linear regression (panel data) and processed with e-views. The results of this study show that education and wage variables have a positive and significant impact, while health variables have a negative and insignificant effect on labor productivity. However, all three variables have a significant effect partially.